2015
DOI: 10.1103/physrevlett.114.246402
|View full text |Cite
|
Sign up to set email alerts
|

Bad-Metal Behavior Reveals Mott Quantum Criticality in Doped Hubbard Models

Abstract: Bad-Metal (BM) behavior featuring linear temperature dependence of the resistivity extending to well above the Mott-Ioffe-Regel (MIR) limit is often viewed as one of the key unresolved signatures of strong correlation. Here we associate the BM behavior with the Mott quantum criticality by examining a fully frustrated Hubbard model where all long-range magnetic orders are suppressed, and the Mott problem can be rigorously solved through Dynamical Mean-Field Theory. We show that for the doped Mott insulator regi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 46 publications
9
86
0
Order By: Relevance
“…For D = ∞, or in constrained slave-spin theories, ŝ x i is directly related to the fermion double occupancy n i↑ni↓ , see Eq. (12). The latter is manifestly gauge invariant and provides an experimentally accessible [85] Ising order parameter for the Mott transition also at T > 0 [48,[86][87][88].…”
Section: Gauge-invariant Picturementioning
confidence: 92%
“…For D = ∞, or in constrained slave-spin theories, ŝ x i is directly related to the fermion double occupancy n i↑ni↓ , see Eq. (12). The latter is manifestly gauge invariant and provides an experimentally accessible [85] Ising order parameter for the Mott transition also at T > 0 [48,[86][87][88].…”
Section: Gauge-invariant Picturementioning
confidence: 92%
“…Unlike the hole-doped superconductivity, the electrondoped superconductivity shows very abrupt and discontinuous (first-order-like) transition. Although the firstorder transitions are not observed in this study, they may appear at extremely low temperatures because of large U/t as shown in the DMFT calculations [20]. This asymmetry may be attributable to the difference of their noninteracting band structures and resultant single-particle spectral functions in the Mott insulating state, where t exists only for one diagonal (κ-Cl), or for both diagonals (cuprates) of the sites.…”
Section: Resultsmentioning
confidence: 55%
“…We have found that the BM behavior at high temperatures persists in almost all doping levels, while the pseudogap behavior at low temperatures is quite bandstructure dependent, implying the different energy scales and mechanisms governing these two behaviors. [20], where the temperature is normalized with TMIR, temperature at which the resistivity reaches ρMIR for δ = 20%.…”
Section: Resultsmentioning
confidence: 99%
“…The second cut in the upper panel at constant U = 3.06 along the µ-axis shows the coexistence region delimited by µ C1 (T ) and µ C2 (T ); a corresponding plot for the one-orbital model can be found in the supplementary material of Ref. 48. All of the results for the twoorbital model with density-density interaction (3) that will be presented in the following were calculated in this plane in parameter space.…”
Section: A Phase Diagrammentioning
confidence: 99%